Perang Saudara Amerika Pada Tahun 1861-1865 Dan Pengaruhnya Terhadap Perkembangan Perekonomian Amerika - Hanifah Nur Liani; Eko Ribawati; Tubagus Noeriman (LPPM Politeknik Pratama, 2023)
This research discusses the influence of the civil war in America that occurred in 1861-1865 and its influence on economic development in America itself. The civil war that occurred in the superpower, namely America, took place from 1861 to 1865. Known as the Civil War, this war involved states in America, namely in the southern and northern regions. Where 11 countries in the southern region have proclaimed themselves under the leadership of a president named Jefferson Davis, while the American countries in the north have proclaimed themselves as union parties with the leadership held by Abraham Lincoln. Every war definitely has positive and negative impacts on all areas within the country itself, including the economic sector in America which is affected or impacted by the civil war. Due to this war, many countries were affected or affected by the war, one of which was the region in the south which was indirectly affected or impacted by the civil war in America. The southern region in America experienced the greatest losses from the war, starting with many plantations being destroyed due to the impact of the war itself. Because the countries in southern America were most affected by the war, this region must be immediately restored because in the American region, plantations are the main economic source for the survival of the country. In studying this problem, researchers used qualitative research methods and were supported by several related literature sources that supported the research.